Analisis Tingkat Penguasaan Teknik Dasar Bola Tangan Pada Siswa SMA Negeri 14 Gowa - Achmad Karim (Program Studi Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the level of mastery of handball basic techniques among students at SMA Negeri 14 Gowa. This research employed a descriptive quantitative approach with a total sample of 30 male students from the sports extracurricular program selected through purposive sampling technique. Data collection was conducted using handball basic technique tests which included passing, catching, dribbling, and shooting techniques. The data analysis technique used descriptive statistics with percentage calculations and categorization of results. The research findings showed that the level of mastery of handball basic techniques among students at SMA Negeri 14 Gowa is in the moderate category with an average score of 68.5 percent. Specifically, passing technique achieved 72 percent (good category), catching technique 70 percent (good category), dribbling technique 65 percent (moderate category), and shooting technique 67 percent (moderate category). These results indicate that students need additional training programs to improve their handball basic technique mastery, particularly in dribbling and shooting techniques.